2015
DOI: 10.1111/1742-6723.12500
|View full text |Cite
|
Sign up to set email alerts
|

Management of mental health patients in Victorian emergency departments: A 10 year follow‐up study

Abstract: Despite increasing MH-related presentations, changes in ED practice have allowed improvements in delivery of care through a shortened ED length of stay and the virtual elimination of very long stays over 24 h. However, there continues to be significant variability in management and performance across hospital sites. Identifying which interventions lead to standout site performance, and subsequent application more broadly, may improve future ED delivery of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…There is little evidence that these increases in MH ED presentations are due to increasing prevalence of mental health disorders in the community. Australian national health survey data suggest prevalence of mental illness is unchanged in Australia from 2001 to 2014 . A systematic review of the global prevalence of anxiety and major depressive disorders found no increase between 1990 and 2010 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence that these increases in MH ED presentations are due to increasing prevalence of mental health disorders in the community. Australian national health survey data suggest prevalence of mental illness is unchanged in Australia from 2001 to 2014 . A systematic review of the global prevalence of anxiety and major depressive disorders found no increase between 1990 and 2010 .…”
Section: Discussionmentioning
confidence: 99%
“…National health surveys and administrative data analyses do not suggest that the prevalence of mental health in the community has changed . However, rates of mental health‐related ED (MH ED) presentations have been shown to be increasing …”
Section: Introductionmentioning
confidence: 99%
“…High ED utilization rates were reported in a 2005 to 2007 study of 427 at-risk youths who injected MAP in Vancouver, Canada [ 38 ]. A comparative study performed 10 years apart (2004 and 2013) of mental health presentations to EDs in Victoria, Australia, found that the number of patients with concurrent MAP exposure more than doubled from 2.2 to 4.3% [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in mental health presentations via the ED is correlated to the ongoing decrease in mental health funding within community services as well as the integration of mental health services with general services (Alarcon Manchego et al . ; Shafei et al . ).…”
Section: Introductionmentioning
confidence: 99%